Penyalahgunaan Peran Aparatur Sipil Negara (ASN) dalam Electoral Misconduct pada Pilkada di Indonesia - Surya Yudha Regif; Andre Pattipeilohy (Badan Pengawas Pemilihan Umum, 2023)
This study was conducted through a literature review method (library research), gathering, analyzing, and organizing data from previous research sources such as scientific articles, journals, and books. The focus of the research is on the misuse of the role of Civil Servants (ASN) in electoral misconduct during the 2020 Regional Head Elections (Pilkada) in Indonesia. This phenomenon encompasses the politicization of bureaucracy through the misuse of the ASN's role by the candidates for regional head. Findings indicate that the practice of Electoral Misconduct results in the misuse of the ASN’s role, which affects the integrity and objectivity of the ASN, leading to violations of the bureaucratic apparatus code of ethics. Despite the existence of established sanctions, both light and severe, ASNs are still involved in practical political practices. This involvement occurs due to temptations like bonds of brotherhood and promises of a better career. Although Government Regulation (PP) Number 94 of 2021 has been issued to maintain the neutrality of ASN, there is still potential involvement in unethical practices. The study also found that this behavior reflects the misuse of the ASN’s role and degradation of morality and ethics within the bureaucracy. The close relationship between politicians and bureaucrats becomes a central challenge, often determining the success or failure of governance. This dynamic is exacerbated by the dominance of pragmatic and materialistic values that overshadow ethical and moral principles.